Swamp Angel - Isaacs, Anne.; Zelinsky, Paul O. (New York : Dutton Children's Books, 1994)
Along with other amazing feats, Angelica Longrider, also known as Swamp Angel, wrestles a huge bear, known as Thundering Tarnation, to save the winter supplies of the settlers in Tennessee.
Wilson's Children
Elem. School Library Collection
Caldecott Medal/Honor
5.3
K-3
Keywords: Tall tales; Frontier and pioneer life -- Tennessee -- Fiction; Tennessee -- Fiction; Tall tales; Frontier and pioneer life -- Tennessee -- Fiction; Tennessee -- Fiction